2004
DOI: 10.1074/jbc.m305838200
|View full text |Cite
|
Sign up to set email alerts
|

CHIP-Hsc70 Complex Ubiquitinates Phosphorylated Tau and Enhances Cell Survival

Abstract: The microtubule-binding protein tau has been implicated in the neurofibrillary pathology of Alzheimer's disease. Within affected cells, ubiquitinated and hyperphosphorylated tau assembles into massive filamentous polymers. Eventually these tangle-bearing neurons die. The formation of neurofibrillary tangles closely parallels the progression and anatomic distribution of neuronal loss in Alzheimer's disease, suggesting that these lesions play a role in the disease pathogenesis. Mutations in the human tau gene ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
345
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(360 citation statements)
references
References 39 publications
14
345
0
1
Order By: Relevance
“…176 The HSP70 co-chaperone CHIP (the acronym stands for the carboxyl terminus of the Hsc70-interacting protein) functions as the primary E3-ligase in ubiquitin-dependent tau clearance. [177][178][179][180] In line with the important function of CHIP in tau clearance, increased tau accumulation was reported in CHIP knock-out mice. 178 Activation of the co-chaperone CHIP could prove to be an attractive drug target, especially because it also stabilizes full length APP against secretase cleavage.…”
Section: Tau Clearancementioning
confidence: 76%
“…176 The HSP70 co-chaperone CHIP (the acronym stands for the carboxyl terminus of the Hsc70-interacting protein) functions as the primary E3-ligase in ubiquitin-dependent tau clearance. [177][178][179][180] In line with the important function of CHIP in tau clearance, increased tau accumulation was reported in CHIP knock-out mice. 178 Activation of the co-chaperone CHIP could prove to be an attractive drug target, especially because it also stabilizes full length APP against secretase cleavage.…”
Section: Tau Clearancementioning
confidence: 76%
“…One of these CAP substrates is the microtubule binding protein tau that forms neurofibrillary tangles in Alzheimer patients and other tauopathies following its hyperphosphorylation (Brandt and Leschik, 2004). Hyperphosphorylated tau is a client of the Hsc/Hsp70 and Hsp90 chaperone network and is targeted for proteasomal degradation by CHIP (Shimura et al, 2004;Dickey et al, 2007). An Hsp90 inhibitor that is able to cross the blood-brain barrier (e.g., EC102) induces tau degradation through CHIP-mediated CAP in cellbased assays and facilitates the disposal of aberrant tau in a transgenic mouse model of tauopathy (Dickey et al, 2007).…”
Section: Cap: Chaperone-assisted Proteasomal Degradationmentioning
confidence: 99%
“…Recently, CHIP has been implicated in progression of the pathophysiological conditions of various neurodegenerative diseases. 8,9,11,12,28,46,47 However, the molecular mechanisms regulating the functions of CHIP in these pathophysiologic conditions are not clearly elucidated. In the present study, we identify that CHIP and Cdk5 act as critical factors to regulate the level of the toxic protein, tAIF, during oxidative stress-induced neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been demonstrated that CHIP prevents neuronal cell death through ubiquitination and subsequent degradation of its substrates including mutant superoxide dismutase 1, α-synuclein, tau, hyperphosphorylated tau, NAD(P)H:quinone oxidoreductase 1, ataxin-1 and leucine-rich repeat kinase 2 in neurodegeneration. 22,[24][25][26][27][28]46 However, it has not been clearly defined whether there may exist a sequential regulatory pathway between Cdk5 and CHIP governing neurodegeneration. More specifically, it has not been determined whether and how CHIP phosphorylation by activated Cdk5 regulates neuronal cell death.…”
Section: Discussionmentioning
confidence: 99%